Development of Web-Based Vehicle Service Application Program on CV X In Bekasi - Aldo Hermaya Aditiya Nurkarsa (Politeknik Siber Cerdika Internasional, 2020)
The increasing number of motorized vehicles, followed by the addition of new brands and types of vehicles, is certainly one of the factors causing the development of the automotive world in Indonesia and reflects the increasingly fierce competition in the automotive world. The research was conducted at CV X Bekasi with qualitative descriptive research methods. Data obtained from interviews the data sources were obtained from documents and informants. Research informants were managers, staff and main documents of CV X. Data analysis was carried out using interactive analysis techniques, which included data collection, data presentation, data reduction and conclusion drawing. So far, the manufacture of work orders is still manual (handwritten), so there are still frequent errors in customer service and data. Often the wrong number of spare parts causes the car repair process to be hampered. Can provide output in the form of Work Orders (SPK), Invoices and Reports.